Experimental-clinical study of carbon biomaterials application in orthopedics and traumatology (literature review) - Korzh, Mykola; Dedukh, Ninel; Tyazhelov, Olexiy; Chzhou, Lu (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Based on analysis of 60 literature sources and own studies found that different forms of carbon are non-toxic and safe, with adequate supply mechanical strength. Carbon biomaterials are non-magnetic, they do not cause allergic reactions, local and systemic reactions. In the culture of osteoblasts and in animal experiments after implantation of carbon biomaterial in bone defect identified it’s osteointegration and high biocompatibility. Implants made of carbon composite materials is not inferior in mechanical and biological characteristics of different artificial biomaterials, but have much lower cost. Carbon has electrical conductivity. The use of various forms of carbon implants makes it possible to optimize reparative osteogenesis, to decrease patient stay, to monitor the operated portion of the skeleton using MRI, it makes possible postoperative radiotherapy and electrotherapy during rehabilitation. In terms of physical, chemical and mechanical properties, biological inertness of carbon are unique biomaterials, including bone implants can be made of any shape and size. Well established in the regeneration of bone and carbon coating of metal implants. Developments in nanotechnology have led to the creation of nanotubes based on carbon, the use of which is prospective and empowers regeneratory medicine due to their combination with cell transplants, collagen and hyaluronic acid. Biomaterials based on carbon can saturate medications, expanding their use in medicine.